Formulation and validation of Candesartan cilexetil-loaded nanosuspension to enhance solubility - Sarmad Al-Edresi; Karrar Albo Hamrah; Abulfadhel Al-Shaibani (Pensoft Publishers, 2024)
The following research aimed to enhance solubility by loading candesartan cilexetil into nanosuspension. Candesartan cilexetil-loaded nanosuspension was prepared with the aid of Design-Expert® software. A technique of solvent evaporation was employed to produce nanosuspensions from hydroxyl propyl methyl cellulose (HPMC E5), polyvinyl pyrrolidone (PVP K-30), and poloxamer (PXM 188). The optimised nanosuspensions' particle size and polydispersity index (PDI) were 64.65 nm and 0.059, respectively. The entrapment efficacy (EE %) and drug loading (DL %) were 86.75 and 10.17%, respectively. The atomic force microscopy (AFM) revealed spherical and smooth nanoparticles. The Fourier transform infrared spectroscopy (FTIR) and differential scanning calorimetry (DSC) revealed pure, crystalline and conjugated drugs inside the nanosuspension. The release study confirmed 90% release within 10 min. No significant changes in particle sizes over three months were found, indicating stable nanoparticles. Saturated solubility of the candesartan cilexetil powder and loaded nanosuspension was 63.3 ± 6 and 344.7 ± 16 µg.ml-1, respectively, revealing more than five times increase in solubility. Candesartan cilexetil-loaded nanosuspensions were successfully prepared using different combinations of PVP K-30, HPMC E-5 and PXM 188 in various concentrations. Solubility was enhanced by loading the payload into nanosuspensions.